Tonically Active α2 Subunit-Containing Glycine Receptors Regulate the Excitability of Striatal Medium Spiny Neurons - Molchanova, Svetlana M.; Comhair, Joris; Karadurmus, Deniz; Piccart, Elisabeth; Harvey, Robert J.; Rigo, Jean-Michel; Schiffmann, Serge N.; Brône, Bert; Gall, David (Frontiers in Molecular Neuroscience, 2018)
Medium spiny neurons (MSNs) of the dorsal striatum represent the first relay of cortico-striato-thalamic loop, responsible for the initiation of voluntary movements and motor learning. GABAergic transmission exerts the main inhibitory control of MSNs. However, MSNs also express chloride- permeable glycine receptors (GlyRs) although their subunit composition and functional significance in the striatum is unknown. Here, we studied the function of GlyRs in MSNs of young adult mice. We show that MSNs express functional GlyRs, with 2 being the main agonist binding subunit. These receptors are extrasynaptic and depolarizing at resting state. The pharmacological inhibition of GlyRs, as well as inactivation of the GlyR 2 subunit gene hyperpolarize the membrane potential of MSNs and increase their action potential firing offset. Mice lacking GlyR 2 showed impaired motor memory consolidation without any changes in the initial motor performance. Taken together, these results demonstrate that tonically-active GlyRs regulate the firing properties of MSNs and may thus affect the function of basal ganglia.